2018
DOI: 10.1186/s13104-018-3380-z
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic performance of direct wet mount microscopy in detecting intestinal helminths among pregnant women attending ante-natal care (ANC) in East Wollega, Oromia, Ethiopia

Abstract: ObjectiveThe aim of this study was to evaluate the diagnostic performance of direct wet mount microscopy compared to formalin ether concentration (FEC) technique in detecting intestinal helminths in pregnant women.ResultsThe total prevalence of intestinal helminths was 18.8% (70/372) by direct wet mount microscopy and 24.7% (92/372) by FEC technique (P < 0.001). The sensitivity, negative predictive value (NPV) and test efficiency (TE) of direct wet mount microscopy in diagnosing intestinal helminths was 76, 92… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 16 publications
4
16
0
Order By: Relevance
“…Moreover, the presence of large stool debris materials in the DWMM may conceal the parasitic ova. The sensitivity of DWMM in this study (37%) is similar with other studies done in Ethiopia (25,27). This suggests that DWMM has resulted in around 63% false negative reports during hookworm diagnosis.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, the presence of large stool debris materials in the DWMM may conceal the parasitic ova. The sensitivity of DWMM in this study (37%) is similar with other studies done in Ethiopia (25,27). This suggests that DWMM has resulted in around 63% false negative reports during hookworm diagnosis.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, DWMM is solely used in almost all health care facilities in Ethiopia and other developing countries due to its low cost, and easy procedure. Nevertheless, it is undoubtedly known that the sensitivity of DWMM is poor (25,26). In spite of this, there are little studies that have evaluated the clinical sensitivity of DWMM compared to other microscopical techniques for the diagnosis of intestinal parasitosis including Hookworm infection.…”
Section: Discussionmentioning
confidence: 99%
“…Direct wet mount of stool has a low sensitivity for detecting light helminthic infections [13]. In two studies, wet mount had detection rates of 18.8% vs. 24.7% for formalin-ether concentration (FEC) [14], and 48.9% vs. 63.1 and 93.7% for FEC and Kato Katz tests, respectively [15]. Nuchprayoon et al (2009) suggest that the simple direct smear is insufficiently sensitive to be used alone for stool parasite screening [16].…”
Section: Introductionmentioning
confidence: 99%
“…This study had concluded that a direct stool wet mount was not a sensitive method for detecting H . nana infection in particular and other intestinal helminths [7].…”
Section: Discussionmentioning
confidence: 99%